Examples of ultrasonic detection of partial discharges in case of 110kV instrument transformers - Milić, Momčilo; Јовановић, Ђорђе; Радин, Весна; Димитријевић, Марко (Proceedings, Electrical engineering institute "Nikola Tesla", 2024)
Instrument transformers represent an important part in case of power plants where they are widely distributed because they play a significant role in measuring and protecting the entire power system. Taking into account the continuous exposure of instrument transformers to ambient and electrical stresses, as well as the fact that their explosions often occur, which directly endangers the operation of electric power facilities and disrupts the stability and continuity of the supply of consumers, there is a need for electrical tests of instrument transformers in order to determine their condition and to be sure they are capable or risky for further operation. One of the methods for testing instrument transformers, whose advantage is that it does not require their disconnection from operation, but the measurements are performed while the tested object is loaded is an acoustic (ultrasound) method and involves placing an acoustic piezo-sensor on the wall of the transformer tank that is grounded and at a safe distance from high voltage, short-term acquisition and subsequent analysis. This is exactly what makes the mentioned method simple to apply in the power plant because it does not require any special interventions or protection. Acoustic detection of partial discharges is generally performed in cooperation with gas chromatographic analysis of insulating oil, which confirms the expressed suspicion of the activity of partial discharges in the insulation of the instrument transformers. The paper will first of all present examples of ultrasonic detection of partial discharges on 110kV instrument transformers where the chemical analysis of the oil sample confirmed the existence of partial discharges.